Quantitative determination of ion distributions in bacterial lipopolysaccharide membranes by grazing-incidence X-ray fluorescence - Schneck, Emanuel; Schubert, Thomas; Konovalov, Oleg V.; Quinn, Bonnie E.; Gutsmann, Thomas; Brandenburg, Klaus; Oliveira, Rafael G.; Pink, David A.; Tanaka, Motomu (Proceedings of the National Academy of Sciences of the United States of America, 2010)
A model of the outer membrane of Gram-negative bacteria was created by the deposition of a monolayer of purified rough mutant lipopolysaccharides at an air/water interface. The density profiles of monovalent (K+) and divalent (Ca2+) cations normal to the lipopolysaccharides (LPS) monolayers were investigated using grazing-incidence X-ray fluorescence. In the absence of Ca2+, a K+ concentration peak was found in the negatively charged LPS headgroup region. With the addition of CaCl2, Ca2+ ions almost completely displaced K+ ions from the headgroup region. By integrating the experimentally reconstructed excess ion density profiles, we obtained an accurate measurement of the effective charge density of LPS monolayers. The experimental findings were compared to the results of Monte Carlo simulations based on a coarse-grained minimal model of LPS molecules and showed excellent agreement.
Gesehen am 20.06.2023